Antibiotic Resistance Pattern of Pathogens Isolated from Clinical Specimens of a Hematology-Oncology Hospital, Ahvaz, 2016-17 - Ali Amin Asnafi; Mandana Ghorbani Kalkhajeh; Leila Kouti; Setareh Razooghi; Kaveh Eslami (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background:Resistance to antibiotics exists around the world. In patients with various types of cancer and also in patients undergoing bone marrow transplantation, infections and febrile neutropenia can be very dangerous. Administration of intravenous ceftazidime alone or in combination with other antibiotics is one of the first empirical treatment regimens. The present study was carried out to determine the resistance pattern of various gram - and gram + microorganisms to different antibiotics at shafa hospital in Ahvaz. Method:This retrospective descriptive cross-sectional study was conducted for a period of one year including all referral clinical specimens from patients with malignancies to Shafa Hospital's Microbiology Laboratory. Isolated bacteria were tested for sensitive antibiotics used in clinics, especially ceftazidime, using a disc diffusion method. Results:After reviewing the records of all patients with malignancies admitted to Shafa hospital from July 2016 toJuly 2017, 310 patients had a recorded culture result (438 cultures in total). The patients were between 1 -85 years old (mean ± SD: 29.96±24.63 years). 50.64% of the patients were male and 49.35% female, mostly admitted to emergency pediatric hematology ward(25.806%). The most common type of malignancy was acute lymphoblastic leukemia(27.096%).Pseudomonasaeroginosa was the most commonisolated pathogen (34.0182%). Only 63 positive cultures containing pseudomonas were tested for antimicrobial resistance, and among these cultures, 55.55% were resistant and 42.85% were sensitive to ceftazidime. Among 9 isolated E.coli cultures, 66.6% were resistant and 33.33% were sensitive to ceftazidime.For Acintobacter and Staph epidermidis, only1 positive culture (out of 33 and 34 respectively) was tested,and in both cases was resistant to ceftazidime. Conclusion:Pseudomonas was the most common pathogen among isolated pathogensand about 56% of positive cultures were resistant or had intermediate sensitivity. Itseems that ceftazidime empiric therapy of infections in patients with malignancies atHematology-Oncology hospital might face high resistance.